THE IMPACT OF LIQUIDITY RATIO ON THE COMPANY VALUE OF INDONESIAN SYARIAH BANKS: CAPITAL STRUCTURE AS A MODERATING VARIABLE FOR THE 2021-2023 PERIOD - Sintia; Nijar Kurnia Romdoni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the impact of liquidity ratios on the corporate value of banking companies with the role of capital structure as a moderating variable. The data used in this study are secondary data obtained from the annual financial reports of Bank Syariah Indonesia listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The method used is multiple regression analysis with a model that includes the interaction between liquidity ratios (Current Ratio) and capital structure (Debt to Equity Ratio) as a moderating variable on corporate value, measured by Price to Book Value (PBV). The results of the study show that liquidity ratios have a positive and significant impact on corporate value, while capital structure has a negative impact on corporate value. In addition, the interaction test shows that capital structure acts as a moderating variable that reduces the positive impact of liquidity ratios on corporate value. These findings indicate that although a high liquidity ratio can increase corporate value, this effect may be diminished if the bank has a capital structure more dominated by debt. This study provides important implications for bank management in balancing liquidity and capital structure to maximize corporate value.